FAKTOR-FAKTOR YANG MEMPENGARUHI AGRESIVITAS PAJAK PADA PERUSAHAAN MANUFAKTUR DI BEI - Indah Hasna Shafa Nadhira; Ferry Suhardjo (E-Jurnal Akuntansi TSM, 2022)
The purpose of this is to obtain the emprical evidence about the factors influencing tax aggresiveness. Independent variables used in this research are liquidity, corporate social responsibility disclosure, firm size, capital intensity, leverage, and profitability. This type of research includes quantitative research using secondary data obtained from company financial statements, company annual reports, and other supporting data. This research used manufacturing companies listed in Indonesia Stock Exchane during 2018-2020. The number of samples in this study were 70 companies with a total of 210 research data that matched the criteria. This research method uses purposive sampling and uses multiple linear regression analysis. The tool used in this research is SPSS 25. The results of this study shows that liquidity and capital intensity have an affect on tax aggressivess while corporate social responsibility disclosure, firm size, leverage and profitability have no effect on tax aggressiveness.